Pengaruh Fraud Pentagon terhadap Financial Statement Fraud - Samino Hendrianto; Nursimah Dara; Masturo Masturo (Journal on Education, 2023)
This study aims to determine the effect of pentagon fraud on financial statement fraud, empirical studies on LQ-45 companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021. Fraud pentagon has several factors that influence the occurrence of financial statement fraud, they are financial stability, external pressure, effectiveness of supervision, change of auditor, financial targets, nature of industry and change of directors. The F-Score model is used in this study to see the potential for financial statement fraud. The method used in selecting the sample in this study was purposive sampling from 22 LQ-45 companies listed on the IDX for the period 2017 – 2021. Hypothesis testing was carried out with panel data using E-views 12.0 software to test the effect of financial stability, external pressure, effectiveness of supervision, change of auditors, financial targets, nature of the industry and change of directors on financial statement fraud. The results of this study indicate that financial stability, and external pressure have an effect on financial statement fraud. Meanwhile, effectiveness of supervision, change of auditor, financial targets, nature of the industry and change of directors have no effect on financial statement fraud.